Development of a Biology-Based Practical Guide Modified Free Inquiry to Grow Teamwork Skill Student - Romadhan, Muhammad Fauzi; Wijaya, Agung; Samiha, Yulia Tri (Peneliti.net, 2024)
The availability of a practicum guide is essential in fostering students' teamwork skills. Based on media needs analysis, it was concluded that the development of a practicum guide based on modified free inquiry is aimed at fostering students' teamwork skills. The objective of this research is to determine the validity, practicality, and effectiveness of the biology practicum guide based on modified free inquiry to enhance students' teamwork skills. This research is categorized as research and development (R&D) using the ADDIE development design (Analyze, Design, Development, Implementation, and Evaluation). The research population consists of biology education students at the State Islamic University of Raden Fatah Palembang. The sampling technique used in this study is purposive sampling. Data analysis for validity and practicality was conducted using Likert scale questionnaires, and effectiveness was measured based on observer questionnaires regarding students' teamwork skills. The validation results showed a media expert percentage of 88.1% with the criterion of very valid, a material expert percentage of 91% with the criterion of very valid, and a language expert percentage of 88.3% with the criterion of very valid. The field practitioners' assessment yielded an average response of 100% in all aspects, categorized as positive, leading to the conclusion that the guide is practical. The effectiveness of the practicum guide was derived from observer assessments, with a result of 83.3%, indicating a very frequent occurrence in fostering students' teamwork skills.